(untitled) (REVISTA NODO, 2019)
Earthen architecture coatings fulfill with several functions such as protection of the structures, regularization of surfaces to make them more hygienic (for not having gaps in which microflora or fauna inhabit) and the water vapor exchange with the surrounding air. This article presents the advances of a research that studies the possible improvement of mud plasters from the recovery of regional traditions derived from the use of the mucilage of the cactus known in Mexico as “nopal” (Opuntia spp.). Results currently found show a remarkable increase in plasticity and adherence of mixtures, a slowdown in the drying time which improves the uniformity of surfaces, a saving of water for mixing and a delay near to 300% on moisture absorption.